Day Labourers' Work Related Injuries: An Assessment of Risks, Choices, and Policies. (18th April 2013) - Meléndez, Edwin; Anne Visser, M.; Valenzuela, Abel; Theodore, Nik
Abstract: Literature and theory surrounding the informal economy in international contexts suggest that informal work arrangements may entail assuming various levels of risk, and that the higher the level of risk in an employment arrangement, the higher the premium paid to the worker. This study is designed to assess if a wage compensation for risk exists within the United States' day labour job market ‐ the most visible sector of the United States' informal economy. Using data from the 2005 National Day Labour Survey we find a statistically significant wage premium indicating that a risk‐wage tradeoff within the day labour informal economy exists. Ultimately, we argue that current policy interventions facilitated through day labour centres into the day labour market appear to be effective in mitigating the risks associated with this type of employment. Evidence of a risk‐wage premium in the day labour market suggests there is an incentive to assume higher levels of risk in work arrangements which presents significant concerns for worker safety. Higher levels of work related risks assumed by day labourers, may be minimized if they receive proper safety training through a formal venue such as a worker centre. Worker centres only serve 20 per cent of all day labourers in the United States, suggesting a need for the establishment of additional worker centres in other connected or industry based work sites, to help mitigate potential work related risks and injuries in the day labour market.